Review: Strategies for using satellite-based products in modeling PM2.5 and short-term pollution episodes. (November 2020) - Sorek-Hamer, Meytar; Chatfield, Robert; Liu, Yang
Highlights: Satellite data have been used for environmental and air quality modelling in the past two decades. This is a brief review of using satellite data for modeling short-term PM2.5 and pollution events. The review can be pursued as a practical guide for modeling air quality with satellite-based products. Abstract: Short-term air pollution episodes motivate improved understanding of the association between air pollution and acute morbidity and mortality episodes, and triggers required mitigation plans. A variety of methods have been employed to estimate exposure to air pollution episodes, including GIS-based dispersion models, interpolation between sparse monitoring sites, land-use regression models, optimization models, line- or area-dispersion plume models, and models using information from imaging satellites, often including land-use and meteorological variables. There has been increasing use of satellite-borne aerosol products for assessing short-term air quality events. They provide better spatial coverage, but currently at the price of low temporal coverage and rather crude spatial resolution. This is a brief review on using satellite data for modeling short-term air quality and pollution events. The review can be pursued as a practical guide for modeling air quality with satellite-based products, as it includes important questions that should be considered in both the study design as well as the model development stages. Progress in this field is detailed and includes published models and their use in environmental and health studies. Both current and future satellite-borne capabilities are covered. It also provides links to access and download relevant datasets and some example R code for data processing and modeling.